On-line assessment of left atrial area and function by echocardiographic automatic boundary detection - Waggoner, A D; Barzilai, B; Miller, J G; Pérez, J E (Circulation (New York, N.Y.), 1993)
Direct assessment of left atrial (LA) function has not been previously performed by noninvasive techniques; rather, LA function has been evaluated only indirectly via the analysis of transmitral flow velocity by Doppler. The recent development of real-time two-dimensional echocardiographic automatic boundary detection suggests that LA dimensions can be measured instantaneously to provide on-line assessment of its systolic and diastolic functions. We performed echocardiographic assessment of LA dimensions and function with automatic boundary detection in 45 patients by using the apical four-chamber view. Thirty-seven patients had structural or functional cardiac abnormalities, 35 patients were in sinus rhythm, and 10 patients had atrial fibrillation. Moderate to severe mitral regurgitation (MR) was noted in 16 patients. We also studied 10 control subjects to assess normal values of LA cavity area and indexes of function. From the instantaneously derived LA area, we derived indexes of systolic atrial expansion and diastolic atrial emptying. There were excellent correlations between the on-line-derived LA areas and those measured off line from videotaped images of conventional echocardiography (r = .91 for end-diastolic and .93 for end-systolic areas; SEE, 4.0 and 3.8 cm2, respectively). Patients in atrial fibrillation had depressed diastolic emptying index (0.17 +/- 0.05) compared with those in sinus rhythm (0.28 +/- 0.12; P < .02). Furthermore, patients with chronic MR exhibited larger LA cavity areas and depressed systolic and diastolic LA function as compared with those without MR. In addition, the Doppler-determined mitral E/A ratio was related to the ratio of early diastolic-to-late diastolic change in LA cavity area (r = .79; SEE 0.6; n = 35). Instantaneous LA cavity area measurement by echocardiographic automatic boundary detection is accurate and feasible in patients with diverse cardiac disorders. Patients with atrial fibrillation had a depressed diastolic emptying index and those with significant mitral regurgitation had depressed systolic expansion index as well. LA functional indexes in both systole and diastole can be derived providing an approach for quantitative evaluations of left atrial-left ventricular interactions based on geometric assessment noninvasively.